GuideLiner Balloon Assisted Tracking (GBAT): A New Addition to the Interventional Toolbox - Basem Elbarouni; Motaz Moussa; Malek Kass; Olga Toleva; Minh Vo; Amir Ravandi (Case Reports in Cardiology)
The use of guide extension catheters, such as GuideLiner, allows for increased guide support and facilitates device delivery in tortuous vessels. In cases which the GuideLiner catheter cannot be advanced even with balloon anchoring technique, we inflate a noncompliant balloon protruding from the GuideLiner catheter at nominal pressure and both the GuideLiner and the balloon are advanced over the coronary guidewire through the tortuous segments. This technique can be applied to 5.5 Fr., 6 Fr., and 7 Fr. GuideLiner catheters. This technique is termed GuideLiner Balloon Assisted Tracking (GBAT).